Non-linear intensification of monsoon low-pressure systems by the BSISO - K. M. R. Hunt; K. M. R. Hunt; A. G. Turner; A. G. Turner (Weather and Climate Dynamics, 2022)
More than half of the rainfall brought to the Indian subcontinent by the summer monsoon is associated with low-pressure systems (LPSs). Yet their relationship with the boreal summer intraseasonal oscillation (BSISO) – the dominant intraseasonal forcing on the monsoon – is only superficially understood. Using reanalysis data, we explore the relationship between the BSISO and LPS intensity, propagation and precipitation, and associated underlying mechanisms.